The temporal pattern of recovery in eccentric hamstring strength post-localised fatigue - Rhodes, D.; Alexander, J.; Greig, M. (SCIREA Journal of Health, 2020)
BACKGROUND: Eccentric hamstring training is a contemporary approach to reducing injury risk in elite footballers. Understanding the temporal pattern of recovery would inform training design. METHODS: 20 male professional football players completed baseline assessments of eccentric hamstring strength at isokinetic speeds of 60, 150 and 300°·s-1. Post-exercise assessments were repeated immediately, +24hrs, +48hrs and +72hrs. Main effects for recovery time and testing speed in average torque (AvT), peak torque (PT) and the corresponding angle (O) were supplemented by regression modelling to describe the temporal pattern of recovery. RESULTS: A main effect for recovery time highlighted greater strength pre exercise, with a quadratic pattern to temporal recovery highlighting minima attained at 35.2 - 41.0 hrs. CONCLUSIONS: Strength parameters are not fully recovered until 82 hrs post localised fatigue, with the angle of peak torque at high speeds recovering at a much slower rate, with implications for training design.